SAP S/4HANA Financial Accounting Configuration : Learn Configuration and Development on an S/4 System - Okungbowa, Andrew (ITpro collection, 2023)
Upgrade your knowledge to learn S/4HANA, the latest version of the SAP ERP system, with its built-in intelligent technologies, including AI, machine learning, and advanced analytics.